KERAWANAN LONGSOR DI KECAMATAN PURABAYA, KABUPATEN SUKABUMI - Prawira, Khairul Yuda; Mataburu, Ilham B.; Hijrawadi, Sony Nugratama (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
The occurrence of landslides in Indonesia has been consistently increasing over the years, particularly in mountainous regions during the rainy season. The country's tectonic conditions, easily brittle volcanic rocks, and wet tropical climate contribute to the heightened potential for landslide disasters. The combination of anthropogenic and natural factors, leading to changes in land use, further exacerbates the risk of landslides, resulting in loss of life and property. This research focuses on the Purabaya Subdistrict, Sukabumi Regency, with the aim of analyzing landslide vulnerability. The analysis results in the creation of a Landslide Vulnerability Map for Purabaya Subdistrict, utilizing a scoring method overlaying rainfall maps, rock type maps, slope inclination maps, land use maps, and soil type maps. A total of 156 land units are identified with classifications of low, moderate, high, and very high landslide vulnerability. Areas with high and very high vulnerability levels encompass 49.52% of the total area, while low vulnerability areas constitute only 6.19%. Purabaya Subdistrict stands out with a dominant high vulnerability level, contributing 49.52% to the total area, whereas low vulnerability areas only cover 6.19%. These findings provide a foundation for landslide disaster risk management in the region.